Cultivo in vitro de células somáticas derivadas de tecido auricular de catetos (Pecari tajacu Linnaeus, 1758) em meio com diferentes suplementações - Santos, Magda Lorena Turbano dos (Universidade Federal Rural do Semi-Árido, 2016)
The maintenance of metabolic activities during the in vitro culture of somatic cells of wild animals, especially collared peccary (Pecari tajacu), is an interesting step in the conservation of these cells for use in nuclear transfer (cloning). In this context, it is necessary to optimize the in vitro culture conditions of somatic cell by establishment of some appropriate supplementations to the media, in order to ensure the maximum preservation of the viable cell characteristics. Therefore, this study aimed to optimize the composition of the culture means of somatic cell derived from ear tissue of collared peccaries, evaluating two concentrations of fetal bovine serum (E1: FBS; 10% vs. 20%) and epidermal growth factor (E2: EGF, 5 ng/mL vs. 10 ng/mL). Thus, tissue fragments from 18 adult animals were submitted to primary culture and subcultures for 40 days until the fourth passage and the resulting cells were analyzed for morphology, adhesion, subconfluence, proliferative activity for developing growth curve for seven days and determining the population doubling time (PDT), viability by trypan blue and functional/metabolic activity by assay 3-[4,5-dimethyl-thiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT). Moreover, in the E1, comparisons as cell adhesion were performed with cells cultured in the presence of bovine serum albumin (BSA, 0.5% and 1.0%). All data were analyzed by ANOVA followed by post hoc test. In the E1, no difference (P>0.05) was observed between the concentrations of FBS for the number of adhered [SFB10: 39/39 vs. SB20: 35/39] and subconfluent fragments [SFB10: 39/39 vs. SB20: 35/39], day all adhered [SFB10: 3.5 vs. SFB20: 3.0], with growth [SFB10: 7.4 vs. SFB20: 7.2] and subconfluent samples [SFB10: 11.8 vs. SFB20: 11.8]. However, significant values were observed in cells cultured in the presence of 20% FBS for viability [SFB10: 85.6% vs. SFB20: 98.2%], PDT [SFB10: 155.4 h vs.77.25 h] and MTT assay [SFB10: 0.57-0.57 vs. SFB20: 0.82-0.99 (D5-D7)]. Additionally, comparisons of supplementation of BSA and FBS confirm the potential FBS cell adhesion. Thus, 20% FBS was used in the following experiment. In the evaluation of the presence of EGF in culture, no difference was observed in the evaluated parameters for the number of attached [EGF0: 31/31 vs. EGF5: 31/31 vs. EGF10: 31/31] and subconfluent fragments [EGF0: 31/31 vs. EGF5: 31/31 vs. EGF10: 31/31] day all adhered [EGF0: 4.9 vs. EGF5: 7.0 vs. EGF10: 3.5] growth [EGF0: 7.2 vs. EGF5: 8.2 vs. EGF10: 7.9] and subconfluent samples [0 EGF: 12.6 vs. EGF5: 16.6 vs. EGF10:12.6], viability [EGF0: 84.3% vs. EGF5: 88.8% vs. EGF10: 87.0%], PDT [EGF0: 69.6 h vs. EGF5: 64.8 h vs. EGF10: 65.3 h] and MTT assay [EGF0: 1.26-1.38 vs. EGF5: 1.06-1.14 vs. EGF10: 1.13-1.16 (D5-D7)]. In all experiments, the growth curves showed clear log and lag phases of development. In conclusion, 20% FBS is suitable for the recovery of somatic cells in vitro; however, EGF does not improve the quality of growing these cells
In vitro culture of somatic cells derived from ear tissue of collared peccary (Pecari tajacu Linnaeus, 1758) in medium with different supplements
Keywords: Conservação; Animais silvestres; Tecido somático; Fonte proteica; Fator mitótico; Conservation; Wild animals; Somatic tissue; Protein source; Mitotic factor; CIENCIAS AGRARIAS::MEDICINA VETERINARIA